2013
DOI: 10.1097/apo.0b013e3182729df0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Forward and Backward Light Scatter in Keratoconus Resulting From Corneal Cross-Linking

Abstract: Unlike TE-CXL, CXL increases the already-elevated stromal backscatter in keratoconus. Forward scatter increases equally for both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…1,16 High levels of corneal light backscatter can be seen even in corneas considered clinically clear. 18 In our study, we found an increase in light backscatter in the central cornea (6 mm in diameter) and total diameter in the KC group . 18 In our study, we found an increase in light backscatter in the central cornea (6 mm in diameter) and total diameter in the KC group .…”
Section: Discussionsupporting
confidence: 53%
“…1,16 High levels of corneal light backscatter can be seen even in corneas considered clinically clear. 18 In our study, we found an increase in light backscatter in the central cornea (6 mm in diameter) and total diameter in the KC group . 18 In our study, we found an increase in light backscatter in the central cornea (6 mm in diameter) and total diameter in the KC group .…”
Section: Discussionsupporting
confidence: 53%
“…The highest UVA intensities are in the center of its beam, and the irradiation intensity declines gradually toward the periphery. 27 The higher intensities in the center produce a deeper CXL effect in the central cornea. This explains why the demarcation line in the peripheral corneal regions typically is more shallow in eyes treated using this device.…”
Section: Discussionmentioning
confidence: 99%
“…Kamaev et al found higher densitometry values in anterior stroma compared to middle and posterior stroma, as well as the central 6 mm zone compared to the more peripheral zones. The decline in riboflavin concentration, intensity of ultraviolet light, and oxygen concentration in deeper stromal layers explains the higher anterior stromal values [ 10 ], whereas the Gaussian beam profile of the conventional UVA-irradiation device with increased irradiation intensity at the center and gradual decline towards the periphery explains the more central haze distribution [ 11 ].…”
Section: Introductionmentioning
confidence: 99%